Meta-analysis of metabolic surgery versus medical treatment for microvascular complications in patients with type 2 diabetes mellitus. Issue 3 (5th February 2018) - Billeter, A T; Scheurlen, K M; Probst, P; Eichel, S; Nickel, F; Kopf, S; Fischer, L; Diener, M K; Nawroth, P P; Müller-Stich, B P
Abstract: Background: This study aimed to examine the effect of metabolic surgery on pre-existing and future microvascular complications in patients with type 2 diabetes mellitus (T2DM) in comparison with medical treatment. Although metabolic surgery is the most effective treatment for obese patients with T2DM regarding glycaemic control, it is unclear whether the incidence or severity of microvascular complications is reduced. Methods: A systematic literature search was performed in MEDLINE, Embase, Web of Science and the Cochrane Central Register of Controlled Trials (CENTRAL) with no language restrictions, looking for RCTs, case–control trials and cohort studies that assessed the effect of metabolic surgery on the incidence of microvascular diabetic complications compared with medical treatment as control. The study was registered in the International prospective register of systematic reviews (CRD42016042994). Results: The literature search yielded 1559 articles. Ten studies (3 RCTs, 7 controlled clinical trials) investigating 17 532 patients were included. Metabolic surgery reduced the incidence of microvascular complications (odds ratio 0·26, 95 per cent c.i. 0·16 to 0·42; P < 0·001) compared with medical treatment. Pre-existing diabetic nephropathy was strongly improved by metabolic surgery versus medical treatment (odds ratio 15·41, 1·28 to 185·46; P = 0·03). Conclusion: In patients with T2DM, metabolic surgery prevented the development of microvascular complications better than medical treatment. Metabolic surgery improved pre-existing diabetic nephropathy compared with medical treatment. Abstract : Surgery is better